Impact of Fintech adoption on operating performance: a study on commercial banks in Bangladesh - Chowdhury, Md. Shurid (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.